Application of Contextual Approach to Student Learning Motivation in Islamic Education Learning Points at SD Negeri Leungah - Rajab, Saifan A. (MANDAILING GLOBAL EDUKASIA, 2024)
In Islamic Religious Education learning, many methods are found that are still conventional and monotonous, where the explanation of the material focuses more on the teacher. This often makes it difficult for students to understand lessons and reduces their level of activity, so that the learning atmosphere becomes less conducive. This research was conducted at SDN Leungah to identify the impact of using a contextual approach in PAI learning. The contextual approach aims to create a more meaningful, relevant and applicable learning experience. By connecting the learning material with students' real experiences and the problems they face every day, this approach is expected to motivate students to be more active in learning and understand Islamic teachings in more depth. This has the potential to shape students' character to have more noble character, in accordance with Islamic values. This research uses a descriptive qualitative approach, with data collection through direct interviews, observation and documentation. Interviews were conducted with teachers and students, while observations were carried out in class to see directly the implementation of the contextual approach in the learning process. The research results show that the application of a contextual approach in PAI learning has a significant impact on students' understanding. Students not only memorize religious concepts, but can also understand the meaning and practical application of Islamic teachings in everyday life. In addition, this approach succeeded in creating a more dynamic and enjoyable learning atmosphere, with increased student active participation in the learning process. Overall, the contextual approach has proven to be effective in improving the quality of PAI learning at SDN Leungah.